Broad color tuning of Bi3+/Eu3+-doped (Ba, Sr)3Sc4O9 solid solution compounds via crystal field modulation and energy transfer. Issue 37 (5th September 2018) - Dang, Peipei; Liang, Sisi; Li, Guogang; Lian, Hongzhou; Shang, Mengmeng; Lin, Jun
Abstract : Color tuning of blue-to-green and green-to-orange was achieved based on the crystal field regulation of Ba 2+ /Sr 2+ substitution and designing Bi 3+ → Eu 3+ energy transfer. Abstract : Controllable luminescence tuning can modify and improve the luminescence performances of phosphor materials and thus promote their application in white light emitting diodes (W-LEDs). Usually, crystal field modulation by constructing solid solutions based on diverse composition substitutions and energy transfers are effective strategies for adjusting the luminescence properties of phosphors. Herein, we report a series of novel emission-tunable Ba3− x Sr x Sc4 O9 : y Bi 3+, z Eu 3+ ( x = 0–3.0, y = 0–0.15, z = 0–0.30) solid solution phosphors synthesized via a high-temperature solid-state route. The XRD patterns and Rietveld refinements were utilized to confirm the phase purity and analyze the structural variation. Cation substitution-dependent color-tunable evolution as a function of Sr content in Bi 3+ -doped Ba3− x Sr x Sc4 O9 was observed and investigated in detail. The regular emission red-shift located in the blue-green region with the increase of Sr content was attributed to the combined effect of the crystal field splitting. Due to the suitable optical band gap (5.50 eV), Bi 3+ ions realized a highly efficient doping in the Sr3 Sc4 O9 matrix. The as-prepared Sr3 Sc4 O9 :Bi 3+ samples were efficiently excited by UV light, and the photoluminescence properties presented obvious preferential-occupation selected excitation phenomenon where the emission peaks had remarkable red-shifts along with increasing the excitation wavelength. In addition, luminescence tuning from green to orange was achieved by designing the energy transfer from Bi 3+ to Eu 3+ ions in the as-prepared Sr2.97− z Sc4 O9 :0.03Bi 3+, z Eu 3+ samples and the corresponding mechanism was proposed. Moreover, the thermal stabilities of the studied phosphors were revealed. According to the distortion calculation of the Ba/Sr crystallographic occupation, the thermal stability is related to the lattice rigidity, which would become much stronger with the reduction of distortion. These results illustrate that the as-prepared Ba3− x Sr x Sc4 O9 :Bi 3+, Eu 3+ phosphors can be potential candidates for color-tunable phosphors applied in UV-pumped W-LEDs.